Lacticaseibacillus paracasei LC86 mitigates age-related muscle wasting and cognitive impairment in SAMP8 mice through gut microbiota modulation and the regulation of serum inflammatory factors - Cai, Yihui; Dong, Yao; Han, Mei; Jin, Manfei; Liu, Huan; Gai, Zhonghui; Zou, Kang (Frontiers in Nutrition, 2024)
Purpose: Chronic inflammation contributes to the decline in muscle strength and cognitive abilities associated with aging. This study aims to clarify the effects of oral administration of Lacticaseibacillus paracasei LC86 on these age-related declines, as well as its impact on the composition of gut microbiota. Methods: Senescence-accelerated mouse prone 8 (SAMP8) mice received a 12-week regimen of LC86 (1×109 CFU/day). Muscle strength was assessed through forelimb grip strength and four-limb hanging tests. Cognitive function was evaluated through behavioral performance tests, and changes in gut microbiota were analyzed. Results: Administration of LC86 significantly enhanced muscle strength, demonstrated by increased grip strength and higher glycogen content in the gastrocnemius muscle (p = 0.041, p = 0.017, and p = 0.000, respectively). Behavioral tests suggested that LC86 mitigated age-related cognitive decline. Furthermore, there was a significant decrease in serum pro-inflammatory cytokines, such as IL-6, TNF-α, and MCP-1 (p = 0.002, p = 0.000, and p = 0.005, respectively), and an elevation in the anti-inflammatory cytokine IL-10 level (p = 0.000). An increase in hepatic antioxidant capacity was observed. Significant changes in the gut microbiota composition were noted, including increased populations of Bifidobacterium and Lactobacillus and decreased levels of Escherichia/Shigella and Bacteroides. Conclusion: The findings suggest that LC86 supplementation mitigates muscle weakness and cognitive impairment in aging SAMP8 mice, potentially through the modulation of inflammation and gut microbiota composition. LC86 emerges as a promising candidate for ameliorating the decline of muscular and cognitive functions associated with aging.